English language curriculum reform strategies: The impact of EMI on students' language proficiency - Mark B. Ulla; Junifer L. Bucol; Pongsathorn Dechatiwongse Na Ayuthaya (Ampersand, 2022)
Language curriculum reform can be challenging and demanding. However, it is crucial for the language teaching and learning process. In Thailand, while the reforms in Thai language education aim to address the country's language proficiency problem, there have been limited studies investigating how these reforms are implemented at an institutional level. This sequential exploratory mixed method research investigated the curriculum policy change in a university in Thailand and how such curriculum policy was implemented, impacting students' language proficiency. Using students' pre-test and post-test scores from 1501 first-year students for the academic year 2019–2020 and interviews with seven university stakeholders, the findings point to the dual function of the curriculum policy change. Such curriculum change, specifically on the implementation of English as a medium of instruction (EMI), is geared toward improving students' language proficiency and the university's internationalization. Based on the findings, we argued that a language curriculum reform should be planned and implemented comprehensively by identifying the grassroots issues to achieve a specific purpose. Implications are discussed, and suggestions are offered.